Strategi Daya Saing dengan Pendekatan Metode SWOT-AHP (Studi Kasus: PT XYZ) - Enggal Sriwardiningsih; Kadek Ray Mahaputra; Kurniawan Aji; Steven Setiawan (STIE Indonesia Banking School, 2017)
PT. XYZ is a company that offers a wide range of electronic care products and services. This study aims to analyze and determine the right strategy for PT. XYZ in improving the competitiveness of enterprises. The research method used is a qualitative method and data collection is done by interview to the officials in PT. XYZ. The method of analysis in this study uses IFE-EFE matrix to analyze PT.XYZ environment. SWOT matrix used to generate alternative strategies and AHP methods used to determine the best strategy for PT. XYZ.